Two new records of bivalve (Mollusca) from Sonadia Island, Bangladesh - Parsha Shanjana Brishti; Kazi Sonia Sultana; Md. Jayedul Islam; Shilpi Sarkar; Md. Baki Billah; Kazi Ahsan Habib (Journal of Fisheries, 2021)
The Sonadia Island, located at the south-east coast of Bangladesh, comprises a wide variety of wetland habitats including mudflats, sand dunes and mangroves which made this island a favoured habitat for diversified molluscan fauna. This paper deals with the new distributional record of two species of marine Bivalvia in Bangladesh- Tellinides timorensis Lamarck, 1818 and Vepricardium coronatum (Schröter, 1786) belonging to the family Tellinidae and Cardiidae respectively. Analysis of taxonomy, diagnosis of shell, geographic distribution and habitat, illustrations of each species and identification characteristics were presented in this paper.